(untitled) (Journal of the College of Basic Education, 2022)
n our research entitled (The day of collection in the Holy Quran) we find the following: The first topic: the concept of the insect language and terminology, the first topic the concept of insectification language and terminology, as well as the statement of the name of the and its evidence. As for the second section, it showed the characteristics of combining the recipe for creation on the Day of Resurrection, including (barefoot and naked, arrogant, liquid, and martyrs). The third topic deals with the difference between the Quran and the Sunnah, and the conditions of the people in the mosque. Then I was asked to mention (the land of collection) and the difference between the scholars.